Rancang Bangun Aplikasi Mobile Perhitungan Indeks Massa Tubuh dan Berat Badan Ideal - Bijak Jati Kusuma; Tito Pinandita (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2011)
Technology is growing rapidly, provides an easy way to do various activities. An example is a mobile application for the calculation of body mass index and ideal weight. The first step of making the application is the system requirements analysis, system design, coding, and implementation into a computer program using J2ME programming language. Last step is testing the application using mobile devices, Nokia C2, Nokia 5233 and Nokia N78. By using this application, it will be easy to know the state of a person's weight, while the BBI calculation can be used to find the ideal weight